PRODUKTIVITAS KARKAS SAPI BALI DI TIMOR BARAT NUSA TENGGARA TIMUR - Andy Yumina Ninu (Politeknik Pertanian Negeri Kupang, 2010)
West Timor was known as one of Bali cattle producing area. Bali cattle was kept in extensive and semi-intensive system. A research was conducted to study Carcass Productivity of Bali Cattle. The research was carried out in Kupang-East Nusa Tenggara from March to May 2008. Sixty three Bali cattle comprising twenty eigth male and theerty five female were used in this study. The experiment used a Completely Randomized Factorial Design (2x3). To study carcass productivity, sex class (male and female) and slaughter weight group (<190 kg, 191-220 kg, >220 kg) were used as the factors. The result of this study showed that no interaction effect between sex and slaughter weight on carcass productivity. Male cattle had higher carcass percentage and commercial cut weights than female cattle. Keywords: carcass, Bali cattle